Childrens’ behaviour and physiological parameters at recovery following dental general anaesthesia with and without premedication oral midazolam at Hospital Universiti Sains Malaysia: a preliminary study - Hisham, Abdul Rauf Badrul (2023)
Oral midazolam premedication usually prescribed for controlling behaviour and reducing anxiety of children and the use under general anaesthesia (DGA) on the behavioural and physiological status of uncooperative paediatric patients have not yet been well explored. This study is aimed to evaluate the effect of oral midazolam premedication on recovery behaviour and physiologic parameters of children undergoing DGA. Thirty uncooperative children aged from 2–11 years were involved in this randomised control trial study. Group I: Received 0.5 mg/kg midazolam orally 30 minutes before entering the operation theatre, while Group II: Did not receive any premedication. Their physiologic parameters were measured at the post anaesthesia care unit (PACU). The recovery behaviour was also recorded for the evaluation using the Modified Houpt Behavior Rating Scale. There was no significant differences in all recovery behaviour and physiologic parameters for both groups (p>0.05). No significant association of premedication oral midazolam with successful recovery behaviour (p=0.381). However, an interesting trend of positive recovery behaviour and physiology was observed among children with oral midazolam premedication. More studies with larger sample size are needed to explore the effect of oral midazolam in paediatric DGA as to discover the optimum effect of premedication.